Current-Control Inverter Schemes for a Grid-Connected PV Generator. Issue 1 (June 2021) - Hussein, Hussein A.; Mahdi, Ali J.; Abdul-Wahhab, Thamir M.
Abstract: Photovoltaic Generators (PVGs) are one of the popular renewable energy sources (RESs), which achieve 47% of RES in microgrids. The main components of the proposed system are: (i) a PVG considering extremum operating conditions, the irradiance change is 400-1000 W/m 2 and the temperature change is 25-60 °C; (ii) a DC-DC boost converter used for regulating the variable DC-link voltage via an inner voltage-loop controller (iii) a single-phase H-bridge inverter controlled by an outer current-loop controller for implementing the maximum power point tracking (MPPT) algorithm at grid side; (iv) an inductive power filter for improving the total harmonic distortion (THD) of the grid current. In this paper, the grid current is controlled to follow the maximum power point (MPP) current considering the losses when transferring the DC power to the grid. Two current-loop controllers are implemented, which are: (i) hysteresis current controller (HCC) and PI current controller (PICC). The proposed design is validated in MATLAB/SIMULINK and the simulation results show significant improvement in power quality, Total Harmonic Distortion (THD) of the output grid current is less than 2% and the power factor is close to unity.